Theoretical DFT Study the Opto-electronic Properties of Poly(3,4-Ethylenedioxythiophene) - Al-anber, Mohanned J; Ali, Aqeel M; Al-Mailky, Norri S; Al-Mowali, Ali H (Scientific World, 2013)
Scientific World, Vol. 11, No. 11, July 2013, page 66-69 DOI: http://dx.doi.org/10.3126/sw.v11i11.8555